Hyperuricemia suppresses lumican, exacerbating adverse remodeling after myocardial infarction by promoting fibroblast phenotype transition - Zehao Zhuang; Ao Liu; Jinghong Zhang; Shuangjian Han; Lu Tang; Tingting Yu; Yiping Shi; Hui Li; Heng Yang; Peiyuan Bai; Yanhua Tang (Journal of Translational Medicine)
Abstract Background Hyperuricemia is independently associated with a poor prognosis in patients with myocardial infarction (MI). Furthermore, MI induces activation of the repair response in local fibroblasts, resulting in extracellular matrix accumulation that generates a stable fibrotic scar in the infarcted area. However, researchers have not determined whether hyperuricemia affects fibroblast activation and its involvement in postinfarction cardiac remodeling. Objectives We aimed to trigger hyperuricemia by administering potassium oxonate in a mouse model of MI to evaluate the role of hyperuricemia in MI pathogenesis. Methods Microarray datasets and single-cell sequencing data from gout patients, heart failure patients, and model mice were used to identify the underlying mechanisms responsible for the effect of hyperuricemia on MI progression. A hyperuricemia-related MI mouse model was established. Cardiac function was assessed, followed by sample collection and a uric acid assay. We conducted an enzyme-linked immunosorbent assay, histological detection, immunofluorescence, sequencing data processing, single-cell RNA-seq, and functional enrichment analysis. We then isolated and cultured cardiac fibroblasts and performed Western blotting, quantitative real-time polymerase chain reaction, and shRNA-mediated lumican knockdown assays. Results Hyperuricemia decreased cardiac function, increased mortality, and aggravated adverse fibrosis remodeling in mice after MI. These outcomes were closely related to reduced levels of fibroblast-derived lumican. This reduction activated the TGF-β/SMAD signaling pathway to induce aberrant myofibroblast activation and extracellular matrix deposition in the infarcted area. Furthermore, lumican supplementation or uric acid-lowering therapy with allopurinol alleviated hyperuricemia-mediated abnormal cardiac remodeling. Conclusion Hyperuricemia aggravates postinfarction cardiac remodeling by reducing lumican expression and promoting fibroblast phenotype transition. We highlight the clinical importance of lowering uric acid levels in hyperuricemia-related MI to prevent adverse ventricular remodeling.